2015
DOI: 10.1021/ab500101c
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Insulin-like Growth Factor I Delivery from Trehalose and Silk-Fibroin Microparticles

Abstract: Insulin-like growth factor I (IGF-I) is a strong anabolic peptide with promising therapeutic value in muscle wasting diseases such as sarcopenia. We report a pulmonary IGF-I delivery system deploying silk-fibroin (SF) as carrier and in comparison to trehalose. Both IGF-I delivery systems were characterized regarding IGF-I integrity, IGF-I release profiles and aerodynamic properties. Transepithelial in vitro transport of IGF-I using the pulmonary Calu-3 model cell system followed comparable kinetics and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
(148 reference statements)
0
11
0
Order By: Relevance
“…21,78 As several studies have shown, nano spray drying has only a negligible or marginal influence on product degradation or aggregation. For example, Schultz et al 79 revealed that the activity of insulin-like growth factor encapsulated in trehalose remained unaffected. In another study, Schmid detected a slight decrease in L-lactic dehydrogenase enzyme activity during feed pump circulation.…”
Section: Influence Of Process Parameters On Powder Propertiesmentioning
confidence: 99%
“…21,78 As several studies have shown, nano spray drying has only a negligible or marginal influence on product degradation or aggregation. For example, Schultz et al 79 revealed that the activity of insulin-like growth factor encapsulated in trehalose remained unaffected. In another study, Schmid detected a slight decrease in L-lactic dehydrogenase enzyme activity during feed pump circulation.…”
Section: Influence Of Process Parameters On Powder Propertiesmentioning
confidence: 99%
“…Furthermore, circular dichroism was used (vide supra) [90]. Additionally, morphological changes of solid SF scaffolds or particles can be observed upon crystallization, typically including shrinkage of scaffolds, changes in porosity [41] or altered surface roughness [29,92]. Methanol is typically used to induce the crystallinity [90] through SF dehydration and conformational destabilizing leading to b-sheet formation [41].…”
Section: Crystallinitymentioning
confidence: 99%
“…28,29 In case of non spherical particles, particularly elongated ones, the aspect ratio plays a key role. It is a fact that the cross sectional area of air way from trachea to alveoli decreases progressively causing enormous air resistance during inhalation.…”
Section: In Vitro Lung Deposition Efficiencymentioning
confidence: 99%
“…the alveoli. 28,29 In the case of non spherical particles, particularly elongated ones, the aspect ratio plays a key role. If the smaller dimension (width or thickness) of the elongated particles is below 5 mm, they will reach the alveoli.…”
Section: In Vitro Lung Deposition Efficiencymentioning
confidence: 99%